LONG-TERM OUTCOMES OF VASCULAR GRAFTS IN HEMODIALYSIS ACCESS RETROSPECTIVE COHORT STUDY - BADSHAH, A; HAI, A; KHAN, R; ISMAIL, M; SHAHZAD, M; AYUBI, A (Biological and Clinical Sciences Research Journal, 2024)
Fistulas and grafts are essential for dialysis in patients diagnosed with end-stage renal disease (ESRD). The durability and efficiency of vascular grafts in hemodialysis access remain critical for patient outcomes. Objective: To evaluate the patency rate, complication rate, and efficiency of vascular graft surgery in hemodialysis access among 100 patients in the Department of Vascular Surgery at CMH Rawalpindi. Methods: This retrospective cohort study was conducted at the Department of Vascular Surgery, CMH Rawalpindi, from August 2022 to May 2024. The study analyzed the records of 100 patients treated with vascular grafts for hemodialysis access. Patient and graft characteristics, patency results, graft, and patient survival, as well as complications, were recorded. Long-term results were evaluated based on follow-up data up to five years. Statistical analyses were conducted using appropriate methods to assess patency rates and complication frequencies. Results: The study included 58 male and 42 female patients aged between 25 and 75 years. The primary patency rate was 85% at one year, 70% at three years, and 55% at five years. Complications included infection in 10% of cases, thrombosis in 15%, and stenosis in 20%. Patient satisfaction was high, with 80% reporting improved quality of life post-surgery. Conclusion: Vascular grafts provide effective long-term arteriovenous (AV) access for hemodialysis, offering reasonable primary and secondary patency rates and manageable complications. Close follow-up and timely intervention are essential to maintaining graft function and patient quality of life.